Ulama Perintis Syair Melayu - Ali, As’adi (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2017)
Poetry is an old Malay literary work that rhymes after pantun, seloka, and gurindam. Appeared at the end of the 17th century AD. Pioneered by an Indonesian Sufi cleric. He is from Barus City (present: Singkil, Aceh), living in the late 17th and early 18th centuries. In his lifetime he is a mufti Kesuthanan Islam Aceh Darussalam. The most important element that distinguishes poetry with other old Malay literature is the final sound of his poetry. If the pantun uses the A-B-A-B, and the A-A-B-B cultivation, the verse is A-A-A-A. Another thing that distinguishes it from its predecessor on the content format. Where, pantun or gurindam on the first and second lines in a stanza contains a sentence (introductory) sentence, and the third and fourth lines are the content or message content. While the verse, the four lines in one stanza are all contents, or the content of the message the poet wishes to convey. In addition, in poetry, in a single line can be composed of three words, while in pantun never got a model like this. The inspired verse of the Arabic literary form, syi'ir, the structure and style can not be separated from the influence of the Arab syi'ir. Some of the direct influences of Arabic syi'ir include the ending sounds of poetry, containing the da'wah and teachings of Islam, writing at the beginning of its emergence using Arabic letters in Malay, many using Arabic terms and quotations, and decorated by natural symbolic words which is often used by Arabic Sufi poets.